Farmers Survey to Assess of Yield Loss due to Insect Pests in Maize and their Management Strategies Adopted by Farmers of Baitadi District of Nepal - Joshi, Ganesh Prasad; Bhatta, Kiran Prasad; Thakurathi, Bibek (Journal of Agriculture and Resource Management, 2024)
The loss due to insect-pests is one of the major constraints in crop cultivation. In order to assess the losses due to insect pests, a survey was conducted in Dashrath Chand municipality and Surnaya Rural Municipality of Baitadi district under Prime Minister Agriculture Modernization Project (PMAMP), Maize Zone, Baitadi. A total of 100 household heads were selected among the farmers of maize pocket areas of the Prime Minister Agriculture Modernization Project for interview using a semi-structured questionnaire. The descriptive and comparative analysis was done for the field survey data using Microsoft Excel (MS Excel), and ranking the problems using the Wilcoxon signed rank test using statistical tools Statistical Packages for the Social Sciences (SPSS). Additionally, indexing was used to rank the major insect pests found in the maize field. Results showed that the major problematic insects found in the maize field were fall armyworm (Spodoptera frugiperda), cutworm (Agrotis spp.), maize stem borer (Chilo partellus) and white grub (Phyllophaga spp.) respectively, as ranked by the farmers according to losses caused by them. The indexing identified fall armyworm infestation as the most crucial problem with an index value of 0.85 (I=0.85). Interestingly, the maximum loss was found 37.5% (local variety) and the minimum loss 8.33% (hybrid variety). Farmers responded that the average loss caused by the insect in local and improved varieties was 25.19% and 18.38%, respectively. Thus, it can be concluded that comparatively the local varieties are more affected by insect pests than the improved varieties. All the surveyed farmers were found to be practicing both the physical and cultural methods. However, some farmers (10%) were also found to be using biological method of insect control. None of the farmers in the selected areas were found to be using chemical pesticides. So this research is focused on identifying damage and various management practices that can be adopted to solve the yield loss caused by insect pests.